Analysis of Indirect Speech Acts in Toni Morrison’s ‘Beloved - Sayyad, Ayesha Imran (International Journal of Language, Literature and Culture, 2023)
Speech act theory is a subfield of pragmatics that is concerned with the ways in which words are used not only to present information but also to carry out actions. The Nobel prize winner African American writer Toni Morrison has dealt with the subjects of violence, sacrifice, slavery, identity crisis, racial discrimination and many more throughout all her novels. Present study aims at examining the effects of indirect speech acts in her most celebrated novel ‘Beloved’ which depicts horrible situation of slavery in USA. It seeks to explore the dialogues in above mentioned novel to see how they have been used. The paper adopts Indirect speech act theory developed by J. R. Searle for the analysis. Only some of the highly marked speech acts will be used for the same. Indirect speech acts enable an interlocutor to convey beyond the boundaries of the words used. Searle’s proposition is, in an indirect speech act, the speaker communicates to the hearer more than he actually says by way of relaying on their mutually shared information, both linguistic and non- linguistic, together with the general powers of rationality and inferences on the part of the hearer. The study concludes that speech act theory is the most appropriate instrument to bring out to the fore the hidden meaning and the crucial aspects of the novel, and thereby, will increase the understanding and appreciation of her novels.